The impacts of trade integration on output gowth of Asian Countries - Arunnan, Balasubramaniam (Universiti Malaysia Sarawak (UNIMAS), 2013)
This study examines the impact of trade integration on output growth of the ASEAN-5 countries namely Indonesia, Malaysia, the Philippines, Singapore and Thailand. This study also assesses whether trade integration with China and India has any important impact on their growth performances. In tandem with these objectives, the Cobb-Douglas type of production functions estimated using ARDL Bound Testing approach to assess the long run relationships between regional trade and output growth for the period 1980-2009.